Pengaruh Profitabilitas,Likuiditas dan Ukuran Perusahaan terhadap Nilai Perusahaan - Rodiarta, Eva Anggraini; Muhammad, Maulana Malik (UNIVERSITAS KALBIS, 2024)
This study aims to determine the effect of profitability, liquidity and company size on firm value in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The population used in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample in this study consisted of 34 companiies which were determined by purposive sampling technique. The research method used is panel data regression, model test, classical assumption test, mulltiple linear regression, and hypothesis testing. From the results of the tests and discussions that have been carried out, it can be concluded that profitability, liquidity and firm size have no effect on firm value.